Novel methodology for football rebound test method - Colino, E.; Corral-Gómez, L.; Rodriguez-Rosa, D.; Juárez-Pérez, S.; Garcia-Unanue, J.; González-Rodriguez, A.; Sánchez-Sánchez, J.; Felipe, L. J.; Gallardo, L.; Castillo-Garcia, J. F. (Sensors, 2020)
Assessing and keeping control of the mechanical properties of sport surfaces is a relevant task in sports since it enables athletes to train and compete safely and under equal conditions. Currently, different tests are used for assessing athlete- and ball-surface interactions in artificial turf pitches. In order to make these evaluations more agile and accessible for every facility, it is important to develop new apparatus that enable to perform the tests in an easier and quicker way. The existing equipment for determining the vertical ball behavior requires a complex and non-easily transportable device in which the ball must be fixed to the upper part of the frame in a very precise position by means of a magnet. The rebound height is determined by capturing the acoustic signal produced when the ball bounces on the turf. When extended tests are conducted, the time required to evaluate a single field is too high due to the non-valid trials. This work proposes a novel methodology which allows to notoriously decrease the time of testing fields maintaining the repeatability and accuracy of the test method together with a compact device for improving its mobility and transport. Simulations and experiments demonstrates the repeatability and accuracy of the results obtained by the proposed device, which decreases the non-valid trials and notoriously reduces the time for field evaluation.